An artificial cornea based on PVA hydrogel and preparation method thereof
By using modified chitosan and nano phosphate in artificial cornea, combined with electrostatic spinning and freezing processing technology, the problems of lack of biocompatibility, mechanical properties and optical characteristics of artificial cornea in existing technologies. A safer and more effective artificial corneal implantation is achieved.
Patent Information
- Application Number
- CN202411303409.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The existing artificial cornea has shortcomings in biocompatibility, mechanical properties and optical properties, resulting in prone to complications such as inflammation and infection after implantation.
The artificial cornea based on PVA hydrogel is used. The optical center contains modified shell polysaccharides. The skirt bracket is added with nano -phosphate and cyclical seductive refined carbon nanotubes.
The good biocompatibility, excellent mechanical properties and good optical characteristics of artificial cornea are realized, reducing the occurrence of post -complications after implantation, and improving the antibacterial and anti -inflammatory resistance of the cornea.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of implant materials and artificial organs in medical devices, and in particular to an artificial cornea based on PVA hydrogel and a preparation method thereof. Background Art
[0002] The cornea is one of the tissues that make up the eyeball, and corneal diseases are common and frequently occurring diseases in ophthalmology. The common treatment for corneal diseases is corneal transplantation. Traditional corneal transplantation generally involves transplanting another person's cornea, but corneal resources are scarce, and other people's biological tissues are transplanted into the patient's body during corneal transplantation, which may lead to rejection or infection. Artificial cornea, as a corneal replacement material, can not only largely solve the problem of corneal donor shortage.
[0003] In early artificial corneas, almost the entire part of the artificial cornea is usually formed by dense transparent inorganic materials (such as glass) and transparent resins (such as polymethacrylate). However, this artificial cornea has low adhesion to biological tissues, and mechanical stress is applied to the eyeball, which may easily lead to deviation or infection of the artificial cornea, and it is very difficult to use the artificial cornea for a long time. Based on the above problems, people have studied artificial corneas formed by soft materials or fiber materials with high biocompatibility. However, there are still many problems in the current artificial cornea transplantation. For example, although hydrogel has certain biocompatibility and permeability, its mechanical properties are poor, and it is very easy to be torn during surgical suturing. Even if the artificial cornea is successfully implanted, inflammation will occur due to the poor combination of eye tissue and artificial cornea, and its swelling resistance also needs to be improved.
[0004] In addition to the properties of general hydrogels, polyvinyl alcohol is highly compatible with human tissues, non-toxic, has no side effects, is non-degradable, has stable chemical properties, excellent mechanical properties, and high water content. It is a very potential artificial cornea replacement material. However, its mechanical properties are still somewhat different from those of human cartilage, and it is difficult to obtain sufficient optical properties (such as high transparency, appropriate refractive index or low scattering properties).
[0005] Therefore, there is an urgent need for an artificial cornea with good biocompatibility, good mechanical properties, optical properties and other properties. Summary of the invention
[0006] The purpose of the present invention is to provide an artificial cornea based on PVA hydrogel and a preparation method thereof in view of the deficiencies in the prior art. The artificial cornea has sufficient optical properties, excellent mechanical properties, good biocompatibility and anti-infection, and reduces the occurrence of complications after implantation.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] On the one hand, an artificial cornea based on PVA hydrogel comprises an optical center portion and a skirt support; wherein,
[0009] The optical center portion comprises a composite PVA hydrogel based on PVA and amino acid / caffeic acid modified chitosan;
[0010] The skirt support comprises PVA, amino acid / caffeic acid modified chitosan, nano phosphate and polyethylene glycol hydroxy acid.
[0011] Furthermore, the mass ratio of PVA to amino acid / caffeic acid modified chitosan in the optical center is 100:(8-15), more preferably 100:12.
[0012] Furthermore, the amino acid / caffeic acid modified chitosan is prepared by modifying chitosan with amino acid and caffeic acid; the mass ratio of chitosan, amino acid and caffeic acid is 10:(0.5-1):(0.2-0.3); preferably, the mass ratio of chitosan, amino acid and caffeic acid is 10:0.8:0.26.
[0013] Preferably, the amino acid is selected from any one or a combination of asparagine, glutamine, lysine and tyrosine.
[0014] The amino acid / caffeic acid modified chitosan is prepared by the following method:
[0015] (1) Dissolve amino acids, EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride), and NHS (N-hydroxysuccinimide) in double distilled water at room temperature to obtain an activated amino acid solution;
[0016] (2) dissolving chitosan in acid to obtain a chitosan solution;
[0017] (3) dissolving caffeic acid and EDC in ethanol water to obtain a caffeic acid solution;
[0018] (4) The activated amino acid solution, chitosan solution and caffeic acid solution in steps (1) to (3) are mixed and reacted under nitrogen protection. After the reaction is completed, the pH is adjusted to a weak alkaline state, the product is washed out by dialysis, and freeze-dried to obtain amino acid-modified chitosan.
[0019] Preferably, in step (1), the mass ratio of the amino acid, EDC and NHS is 1:(2-3):(0.5-1).
[0020] Preferably, in step (2), the acid is any one of dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid and acetic acid with a pH of 5 to 5.5.
[0021] Preferably, in step (3), the mass ratio of caffeic acid to EDC is 1:(1.5-3); and the volume ratio of ethanol to water in the ethanol water is (20-60):(40-80).
[0022] Preferably, in step (4), the reaction time is 12 to 24 hours and the reaction temperature is 40 to 50°C.
[0023] Furthermore, in the skirt bracket, the mass ratio of the PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid and nanophosphate is 100:(5-10):(7-12):(5-10); the preferred mass ratio is 100:8:10:7.
[0024] Furthermore, the skirt bracket further comprises cyclodextrin-modified carbon nanotubes, and the addition amount of the cyclodextrin-modified carbon nanotubes is 5-7.5% of the mass of PVA; the cyclodextrin-modified carbon nanotubes are prepared by the following method:
[0025] (1) placing carbon nanotubes in an acid and subjecting them to ultrasonic treatment to obtain carboxylated carbon nanotubes;
[0026] (2) Add carboxylated carbon nanotubes and cyclodextrin into water, add EDC and NHS, react overnight, filter, and wash with water until neutral to obtain cyclodextrin-modified carbon nanotubes.
[0027] Preferably, in step (1), the acid is concentrated sulfuric acid and / or concentrated nitric acid.
[0028] Preferably, in step (1), the cyclodextrin is γ-cyclodextrin.
[0029] Preferably, in step (2), the mass ratio of the carboxylated carbon nanotubes to cyclodextrin is 1:(0.25-0.32).
[0030] On the other hand, the method for preparing the artificial cornea based on PVA hydrogel comprises the following steps:
[0031] S1, dispersing PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid, and nanophosphate in water to form a spinning solution, and preparing a non-woven fabric with a middle through hole as a skirt support by electrospinning;
[0032] S2, mixing PVA, amino acid / caffeic acid modified chitosan, dimethyl sulfoxide and water to obtain a composite PVA hydrogel precursor solution;
[0033] S3, immersing the non-woven fabric in the composite PVA hydrogel precursor solution, freeze-thawing it 4-5 times, so that the PVA composite hydrogel is fixed on the surface of the non-woven fabric to form an optical center, and then washing with water to remove the solvent to obtain the product.
[0034] Furthermore, in step S1, the mass ratio of the total mass of the PVA, amino acid / caffeic acid modified chitosan and nano-phosphate to water is (25-35): (65-75).
[0035] Furthermore, in step S2, the mass ratio of the total mass of the PVA and amino acid / caffeic acid modified chitosan to the mass ratio of dimethyl sulfoxide and water is 1:(5-6):(1-2).
[0036] Furthermore, in step S3, the freeze-thaw treatment process is: freezing at -20 to -30°C for 14 to 16 hours, placing at room temperature for 3.5 to 5 hours, and repeating this process 4 to 5 times to complete the freeze-thaw treatment.
[0037] Furthermore, in step S1, the nonwoven fabric further includes subjecting the composite PVA hydrogel precursor solution to microwave treatment and infrared treatment in sequence before being impregnated with the composite PVA hydrogel precursor solution; the power of the microwave treatment is 140 to 180 W, and the time is 30 to 50 min; the wavelength of the infrared treatment is 780 to 850 nm, and the time is 20 to 30 min. The applicant has found that subjecting the composite PVA hydrogel precursor solution to infrared treatment in advance and then to microwave treatment can help obtain a uniform PVA hydrogel, further improve its mechanical properties, reduce the defect of being easily torn due to poor mechanical strength during surgical suturing, and improve the success rate of artificial cornea implantation.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The present invention provides an artificial cornea based on PVA hydrogel and a preparation method thereof. The artificial cornea has good biocompatibility, high water content, good optical properties, excellent mechanical properties, and the advantages of sterilization and anti-inflammation, and can reduce the occurrence of complications after implantation.
[0040] 2. The artificial cornea based on PVA hydrogel provided by the present invention adds amino acid / caffeic acid modified chitosan in the optical center and the skirt support material. The introduction of amino acids into chitosan helps to enhance its biocompatibility and antibacterial properties, and compensates for the poor mechanical properties of chitosan after absorbing water; the introduction of caffeic acid into chitosan further increases the antibacterial and anti-inflammatory properties of chitosan and reduces the anti-infective property; in addition, the applicant has also found that the simultaneous introduction of amino acids and caffeic acid into chitosan, on the one hand, can greatly improve the antibacterial and long-acting antibacterial properties, and can also enable the modified chitosan and PVA hydrogel to form a more uniform three-dimensional network cross-linked structure, and the mechanical properties are greatly improved, which compensates for the poor mechanical properties of the existing PVA hydrogel and the defect that it is very easy to be torn during surgical sutures, thereby improving safety; on the other hand, it also helps to improve the water content and light transmittance of the PVA hydrogel, so that the artificial cornea has sufficient optical transmittance.
[0041] 3. The artificial cornea based on PVA hydrogel of the present invention adds cyclodextrin-modified carbon nanotubes to the skirt bracket. Compared with the unmodified carbon nanotubes, the modified carbon nanotubes have better compatibility with materials such as PVA, which can enhance the mechanical strength and toughness of the skirt bracket and improve the safety of implantation. In addition, the addition of cyclodextrin-modified carbon nanotubes has a certain synergistic effect with polyethylene glycol hydroxy acid, which can not only greatly enhance the mechanical properties, but also help to improve its hydrophilicity and increase the water content. DETAILED DESCRIPTION
[0042] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present invention.
[0043] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0044] Example 1
[0045] An artificial cornea based on PVA hydrogel, comprising an optical center portion and a skirt support;
[0046] The optical center portion comprises a composite PVA hydrogel based on PVA and amino acid / caffeic acid modified chitosan; the mass ratio of PVA to amino acid / caffeic acid modified chitosan is 100:8;
[0047] The skirt scaffold contained PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid, and nanophosphate in a mass ratio of 100:5:7:5.
[0048] Wherein, amino acid / caffeic acid modified chitosan is prepared by the following method:
[0049] (1) dissolving 0.5 parts by weight of amino acid, 1 part by weight of EDC, and 0.25 parts by weight of NHS in 50 parts by weight of double distilled water to obtain an activated amino acid solution;
[0050] (2) dissolving 10 parts by weight of chitosan in 20 times by weight of hydrochloric acid with a pH of 5.5 to obtain a chitosan solution;
[0051] (3) dissolving 0.2 parts by weight of caffeic acid and 0.35 parts by weight of EDC in 50 times by weight of ethanol water (volume ratio 6:4) to obtain a caffeic acid solution;
[0052] (4) The activated amino acid solution, chitosan solution and caffeic acid solution in steps (1) to (3) are mixed, reacted at 40° C. for 24 h under nitrogen protection, and after the reaction, the pH is adjusted to 7.5. The product is washed out, dialyzed, and freeze-dried to obtain amino acid-modified chitosan.
[0053] This embodiment also provides a method for preparing an artificial cornea based on PVA hydrogel, comprising the following steps:
[0054] S1, dispersing a total of 25 parts by weight of PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid, and nanophosphate in 75 parts of water to form a spinning solution, and preparing a non-woven fabric with a middle through hole as a skirt bracket by electrospinning;
[0055] S2, mixing a total of 10 parts by weight of PVA and amino acid / caffeic acid modified chitosan with 50 parts by weight of dimethyl sulfoxide and 20 parts by weight of water to obtain a composite PVA hydrogel precursor solution;
[0056] S3. Immerse the nonwoven fabric in the composite PVA hydrogel precursor solution, freeze it at -200°C for 16 hours, and then place it at room temperature for 3.5 hours. Repeat this process 4 times to complete the freeze-thaw treatment.
[0057] Example 2
[0058] An artificial cornea based on PVA hydrogel, comprising an optical center portion and a skirt support;
[0059] The optical center portion comprises a composite PVA hydrogel based on PVA and amino acid / caffeic acid modified chitosan; the mass ratio of PVA to amino acid / caffeic acid modified chitosan is 100:12;
[0060] The skirt scaffold contained PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid, and nanophosphate in a mass ratio of 100:8:10:7.
[0061] Wherein, amino acid / caffeic acid modified chitosan is prepared by the following method:
[0062] (1) dissolving 0.8 parts by weight of amino acid, 0.8 parts by weight of EDC, and 0.8 parts by weight of NHS in 50 parts by weight of double distilled water to obtain an activated amino acid solution;
[0063] (2) dissolving 10 parts by weight of chitosan in 20 times by weight of hydrochloric acid with a pH of 5.5 to obtain a chitosan solution;
[0064] (3) dissolving 0.26 parts by weight of caffeic acid and 0.78 parts by weight of EDC in 50 times by weight of ethanol water (volume ratio 6:4) to obtain a caffeic acid solution;
[0065] (4) The activated amino acid solution, chitosan solution and caffeic acid solution in steps (1) to (3) are mixed, reacted at 50° C. for 12 h under nitrogen protection, and after the reaction, the pH is adjusted to 7.5. The product is washed out, dialyzed, and freeze-dried to obtain amino acid-modified chitosan.
[0066] This embodiment also provides a method for preparing an artificial cornea based on PVA hydrogel, comprising the following steps:
[0067] S1, dispersing a total of 35 parts by weight of PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid, and nanophosphate in 65 parts of water to form a spinning solution, and preparing a non-woven fabric with a middle through hole as a skirt bracket by electrospinning;
[0068] S2, mixing a total of 10 parts by weight of PVA and amino acid / caffeic acid modified chitosan with 60 parts by weight of dimethyl sulfoxide and 10 parts by weight of water to obtain a composite PVA hydrogel precursor solution;
[0069] S3. Immerse the nonwoven fabric in the composite PVA hydrogel precursor solution, freeze it at -200°C for 16 hours, and then place it at room temperature for 3.5 hours. Repeat this process 5 times to complete the freeze-thaw treatment.
[0070] Example 3
[0071] An artificial cornea based on PVA hydrogel, comprising an optical center portion and a skirt support;
[0072] The optical center portion comprises a composite PVA hydrogel based on PVA and amino acid / caffeic acid modified chitosan; the mass ratio of PVA to amino acid / caffeic acid modified chitosan is 100:15;
[0073] The skirt scaffold contained PVA, amino acid / caffeic acid-modified chitosan, polyethylene glycol hydroxy acid, and nanophosphate in a mass ratio of 100:10:12:10.
[0074] Wherein, amino acid / caffeic acid modified chitosan is prepared by the following method:
[0075] (1) dissolving 1 part by weight of amino acid, 1 part by weight of EDC, and 1 part by weight of NHS in 50 parts by weight of double distilled water to obtain an activated amino acid solution;
[0076] (2) dissolving 10 parts by weight of chitosan in 20 times by weight of hydrochloric acid with a pH of 5.5 to obtain a chitosan solution;
[0077] (3) dissolving 0.3 parts by weight of caffeic acid and 0.9 parts by weight of EDC in 50 times by weight of ethanol water (volume ratio 6:4) to obtain a caffeic acid solution;
[0078] (4) The activated amino acid solution, chitosan solution and caffeic acid solution in steps (1) to (3) are mixed, reacted at 50° C. for 12 h under nitrogen protection, and after the reaction, the pH is adjusted to 7.5. The product is washed out, dialyzed, and freeze-dried to obtain amino acid-modified chitosan.
[0079] This embodiment also provides a method for preparing an artificial cornea based on PVA hydrogel, comprising the following steps:
[0080] S1, dispersing a total of 35 parts by weight of PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid, and nanophosphate in 65 parts of water to form a spinning solution, and preparing a non-woven fabric with a middle through hole as a skirt bracket by electrospinning;
[0081] S2, mixing a total of 10 parts by weight of PVA and amino acid / caffeic acid modified chitosan with 60 parts by weight of dimethyl sulfoxide and 10 parts by weight of water to obtain a composite PVA hydrogel precursor solution;
[0082] S3. Immerse the nonwoven fabric in the composite PVA hydrogel precursor solution, freeze it at -200°C for 16 hours, and then place it at room temperature for 3.5 hours. Repeat this process 5 times to complete the freeze-thaw treatment.
[0083] Example 4
[0084] The difference from Example 2 is that in this example, the mass ratio of chitosan, amino acid and caffeic acid in the preparation process of amino acid / caffeic acid modified chitosan is 10:0.3:0.1.
[0085] Example 5
[0086] The difference from Example 2 is that in this example, the mass ratio of chitosan, amino acid and caffeic acid in the preparation process of amino acid / caffeic acid modified chitosan is 10:1.2:0.5.
[0087] Example 6
[0088] The difference from Example 2 is that in this example, the mass ratio of PVA to amino acid / caffeic acid modified chitosan in the optical center is 100:5.
[0089] Example 7
[0090] The difference from Example 2 is that in this example, the mass ratio of PVA to amino acid / caffeic acid modified chitosan in the optical center is 100:18.
[0091] Example 8
[0092] The difference from Example 2 is that cyclodextrin nano-modified carbon nanotubes with a mass percentage of 5% of PVA are further added to the skirt bracket of this embodiment; wherein the cyclodextrin nano-modified carbon nanotubes are prepared by the following method:
[0093] (1) placing 1 part by weight of carbon nanotubes in 50 parts by weight of concentrated nitric acid, ultrasonically treating for 20 minutes, washing with water until neutral, and drying to obtain carboxylated carbon nanotubes;
[0094] (2) 1 part by weight of carboxylated carbon nanotubes and 0.25 parts by weight of cyclodextrin were added to 100 parts by weight of water, and 1 part by weight of EDC and 1 part by weight of NHS were added. The mixture was reacted overnight in an ice bath, filtered, and washed with water until neutral to obtain cyclodextrin-modified carbon nanotubes.
[0095] Example 9
[0096] The difference from Example 8 is that in this example, an equal amount of carboxylated carbon nanotubes is used instead of cyclodextrin-modified carbon nanotubes.
[0097] Example 10
[0098] The difference from Example 8 is that in this example, an equal amount of unmodified carbon nanotubes is used instead of cyclodextrin-modified carbon nanotubes.
[0099] Embodiment 11
[0100] The difference from Example 2 is that, in this embodiment, step S2 of preparing an artificial cornea based on PVA hydrogel includes: mixing a total of 10 parts by weight of PVA and amino acid / caffeic acid modified chitosan with 60 parts by weight of dimethyl sulfoxide and 10 parts by weight of water, microwave treatment at 180 W for 30 minutes, and then infrared treatment at a wavelength of 850 nm for 20 minutes to obtain a composite PVA hydrogel precursor solution.
[0101] Example 12
[0102] The difference from Example 2 is that, in this embodiment, step S2 of preparing an artificial cornea based on PVA hydrogel includes: mixing a total of 10 parts by weight of PVA and amino acid / caffeic acid modified chitosan with 60 parts by weight of dimethyl sulfoxide and 10 parts by weight of water, and performing infrared treatment at a wavelength of 850 nm for 20 minutes to obtain a composite PVA hydrogel precursor solution.
[0103] Comparative Example 1
[0104] The difference from Example 2 is that in this comparative example, an equal amount of amino acid-modified chitosan is used instead of amino acid / caffeic acid-modified chitosan; the amino acid-modified chitosan is prepared by the following method:
[0105] (1) dissolving 0.8 parts by weight of amino acid, 0.8 parts by weight of EDC, and 0.8 parts by weight of NHS in 50 parts by weight of double distilled water to obtain an activated amino acid solution;
[0106] (2) dissolving 10 parts by weight of chitosan in 20 times by weight of hydrochloric acid with a pH of 5.5 to obtain a chitosan solution;
[0107] (3) The activated amino acid solution and chitosan solution were mixed, reacted at 50°C for 12 h under nitrogen protection, and the pH was adjusted to 7.5 after the reaction. The product was washed out by dialyzing and freeze-dried to obtain amino acid-modified chitosan.
[0108] Comparative Example 2
[0109] The difference from Example 2 is that in this comparative example, an equal amount of caffeic acid-modified chitosan is used instead of amino acid / caffeic acid-modified chitosan; the caffeic acid-modified chitosan is prepared by the following method:
[0110] (1) dissolving 10 parts by weight of chitosan in 20 parts by weight of hydrochloric acid having a pH value of 5.5 to obtain a chitosan solution;
[0111] (2) dissolving 0.26 parts by weight of caffeic acid and 0.78 parts by weight of EDC in 50 times by weight of ethanol water (volume ratio 6:4) to obtain a caffeic acid solution;
[0112] (3) The chitosan solution and the caffeic acid solution were mixed and reacted at 50°C for 12 h under nitrogen protection. After the reaction, the pH was adjusted to 7.5, the product was washed out by dialyzing, and freeze-dried to obtain amino acid-modified chitosan.
[0113] Comparative Example 3
[0114] The difference from Example 2 is that in this comparative example, an equal amount of unmodified chitosan is used to replace the amino acid / caffeic acid modified chitosan.
[0115] Comparative Example 4
[0116] The difference from Example 2 is that in this comparative example, no amino acid / caffeic acid modified chitosan is added to the artificial cornea.
[0117] Comparative Example 5
[0118] The difference from Example 8 is that in this comparative example, polyethylene glycol hydroxy acid is not added to the skirt bracket.
[0119] Test Example 1
[0120] The artificial corneas obtained in the above examples and comparative examples were tested for light transmittance, water absorption, mechanical properties, and antibacterial properties. The specific testing methods are as follows:
[0121] 1. Light transmittance: Take a sample from the optical center and test the light transmittance in the wavelength range of 400-800nm using a UV spectrophotometer.
[0122] 2. Moisture content test: Take an appropriate amount of swelling equilibrium sample, wipe off the surface moisture and weigh the film weight as W1. After it is completely dried, weigh it as W2 and calculate the moisture content R = (W1-W2) / W1×100%.
[0123] 3. Mechanical properties: Refer to GB / T1040-Determination of tensile properties of plastics to test tensile strength and elongation at break. The sample size is 10mm×40mm. The test is carried out at room temperature at a tensile rate of 30mm / min.
[0124] 4. Corneal suturing: Use two 5-0 sutures to pierce the edges of the two ends of the decellularized artificial cornea respectively, fix the two sutures on the clamps at both ends of the mechanical testing machine respectively, and stretch them toward both ends at a speed of 50 mm / min until the sutures tear the decellularized artificial cornea. Record the maximum pulling force of the sutures tearing the decellularized artificial cornea, which is the suture force.
[0125] 5. Antibacterial
[0126] The antibacterial zone method was used for testing, and the test strains were Staphylococcus aureus, Escherichia coli, and Bacillus subtilis. The antibacterial properties of the samples were tested after being placed for 8 months.
[0127] The test results of the above test are shown in Tables 1 and 2 below.
[0128] Table 1
[0129]
[0130] The results showed that the artificial cornea prepared by the method of the present invention had a transmittance of more than 90% at 700nm, good optical properties, a water content of more than 80%, transmittance and water content similar to those of a normal human cornea, a tensile strength of about 3MPa, an elongation at break of more than 400%, excellent mechanical properties, a maximum load of corneal suture of more than 1MPa, and was able to withstand the cutting force of suture thread sutures, thereby improving the success rate and safety of implantation.
[0131] Table 2
[0132]
[0133] The results show that the diameter of the inhibition zone of the artificial cornea prepared by the method of the present invention against Staphylococcus aureus, Escherichia coli, and Bacillus subtilis can reach more than 30 mm, and it has excellent antibacterial properties. The diameter of the inhibition zone is still higher than 20 mm after 14 days, and the antibacterial property is long-lasting. Compared with Example 2, the antibacterial properties of Examples 4-8 and Comparative Examples 1-4 at 14 days are significantly reduced, which shows that the addition of amino acid / caffeic acid modified chitosan not only helps to improve the antibacterial property of the artificial cornea, but also gives it long-lasting antibacterial properties.
[0134] Test Example 2
[0135] Cytotoxicity assay
[0136] The in vitro cytotoxicity test was performed using the MTT colorimetric method. The specific steps are as follows:
[0137] (1) Preparation of sample extract
[0138] Under sterile operation, take the sample 90cm 2 , according to 6cm 2 15.00 mL of extraction medium (MEM containing 10% fetal bovine serum (1xMEM)) was added at a ratio of 1:1 to 1:1. The extracted stock solution was obtained after extraction at 37°C for 24 h, and filtered with a 0.22 um sterile filter membrane before use.
[0139] Positive control group: 10% fetal bovine serum MEM (1xMEM) containing 5% DMSO.
[0140] Blank control group: 10% fetal bovine serum MEM (1xMEM).
[0141] (2) Set up a blank group, a negative control group, a positive control group, and a sample group. Each group has 6 parallel wells (96-well cell culture plate). 4 A cell suspension of 100 mL / mL was inoculated into each parallel well, and each well was inoculated with 100 mL of cell suspension, and cultured in an incubator at 37°C containing 5% CO for 24 h. After the culture was completed, the original culture medium was discarded, and fresh cell culture medium was added to the blank control group, the positive control solution was added to the positive control group, and the sample extract was added to the sample group, with 100 mL inoculated into each well; then the culture was continued for 72 h. After the culture was completed, the morphology of the cultured cells was observed under a microscope; 20 mL of MTT with a density of 5 g was added to each parallel well, and the culture medium was discarded after continuing to culture for 4 h, and 150 L of DMSO was added. The above DMSO solution containing cells was placed on an oscillator for 10 min, and its absorbance at wavelengths of 570 nm and 630 nm was determined with an enzyme marker to calculate the proliferation rate RGR=A / A0×100%; wherein A is the absorbance of the sample or positive control group; A0 is the absorbance of the blank control group.
[0142] (3) The grading and evaluation criteria for cytotoxic reactions are shown in Table 3.
[0143] Table 3
[0144]
[0145] (4) The test results are shown in Table 4 below.
[0146] Table 4
[0147]
[0148] The results show that amino acid / caffeic acid modified chitosan is not added to the artificial cornea of Comparative Example 4. Compared with Comparative Example 4, the artificial corneas of Comparative Examples 1-3 have a certain inhibitory effect on cell proliferation, while the artificial cornea prepared by the method of the present invention has a significant promoting effect on cell proliferation, and the cell proliferation rate is above 90%. That is, the artificial cornea provided by the present invention has good biocompatibility and can ensure the normal growth of cells.
[0149] In addition, after the acute systemic toxicity test, after the artificial corneal extract provided by the present application was injected into mice, the mice were normal, did not show obvious symptoms, and had no acute systemic toxicity reaction.
[0150] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An artificial cornea based on PVA hydrogel, comprising an optical center portion and a skirt support; wherein: The optical center portion comprises a composite PVA hydrogel based on PVA and amino acid / caffeic acid modified chitosan; the mass ratio of the PVA to the amino acid / caffeic acid modified chitosan is 100:(8-15); The amino acid is selected from any one or a combination of asparagine, glutamine, lysine, and tyrosine; The amino acid / caffeic acid modified chitosan is prepared by the following method: (1) dissolving amino acid, EDC 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and NHS N-hydroxysuccinimide in double distilled water at room temperature to obtain an activated amino acid solution; (2) dissolving chitosan in acid to obtain a chitosan solution; (3) dissolving caffeic acid and EDC in ethanol water to obtain a caffeic acid solution; (4) mixing the activated amino acid solution, chitosan solution and caffeic acid solution in steps (1) to (3), reacting under nitrogen protection, adjusting the pH to weak alkalinity after the reaction, eluting the product by dialysis, and freeze-drying to obtain amino acid modified chitosan; The skirt support comprises PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid and nanophosphate in a mass ratio of 100:(5-10):(7-12):(5-10); The artificial cornea based on PVA hydrogel is prepared by the following method: S1, dispersing PVA, amino acid / caffeic acid modified chitosan, polyethylene glycol hydroxy acid, and nanophosphate in water to form a spinning solution, and preparing a non-woven fabric with a middle through hole as a skirt support by electrospinning; S2, mixing PVA, amino acid / caffeic acid modified chitosan, dimethyl sulfoxide and water to obtain a composite PVA hydrogel precursor solution; S3, immersing the non-woven fabric in the composite PVA hydrogel precursor solution, freeze-thawing it 4-5 times, so that the PVA composite hydrogel is fixed on the surface of the non-woven fabric to form an optical center, and then washing with water to remove the solvent to obtain the product.
2. The artificial cornea based on PVA hydrogel according to claim 1, characterized in that: The amino acid / caffeic acid modified chitosan is prepared by modifying chitosan with amino acids and caffeic acid; The mass ratio of chitosan, amino acid and caffeic acid is 10:(0.5-1):(0.2-0.3).
3. The artificial cornea based on PVA hydrogel according to claim 1 or 2, characterized in that: The skirt support also contains cyclodextrin-modified carbon nanotubes; the added amount of the cyclodextrin-modified carbon nanotubes is 5-7.5% of the mass of the PVA.
4. The artificial cornea based on PVA hydrogel according to claim 3, characterized in that: The cyclodextrin modified carbon nanotubes are prepared by the following method: (1) placing carbon nanotubes in an acid and subjecting them to ultrasonic treatment to obtain carboxylated carbon nanotubes; (2) Add carboxylated carbon nanotubes and cyclodextrin into water, add EDC and NHS, react overnight, filter, and wash with water until neutral to obtain cyclodextrin-modified carbon nanotubes.
5. The artificial cornea based on PVA hydrogel according to claim 4, characterized in that: The mass ratio of the carboxylated carbon nanotubes to cyclodextrin is 1:(0.25-0.32).
6. The artificial cornea based on PVA hydrogel according to claim 1, characterized in that: The freeze-thaw treatment process is: freezing at -20 to -30°C for 14 to 16 hours, placing at room temperature for 3.5 to 5 hours, and repeating this process 4 to 5 times to complete the freeze-thaw treatment.
Citation Information
Patent Citations
Preparation method of functional polymethyl methacrylate, cyclodextrin and carbon nano tube composite nanofiber membrane
CN105297286A
Arginine modified chitosan and preparation method thereof and injectable antibacterial hydrogel
CN106832060A